A Method for Evaluating Coke Hot Strength. Issue 1 (8th August 2012) - Haapakangas, Juho; Uusitalo, Juha; Mattila, Olli; Kokkonen, Tommi; Porter, David; Fabritius, Timo
Abstract The strength of coke is of major importance for efficient blast furnace operation. There are only a few studies related to compressive coke hot strength, possibly due to experimental difficulties. In this work, it has been demonstrated that the Gleeble thermomechanical simulator is suitable for evaluating coke hot strength and offers many benefits compared to purpose‐built devices reported in the literature. This finding could open coke hot strength research to a wider number of scientists. The compressive hot strength of coke was evaluated at 1000 and 1600°C by testing 50 samples at both temperatures. The yield strength and ultimate strength of the coke were, respectively, 46 and 20% lower at 1600°C than 1000°C. Stress–strain curves showed that the coke was brittle at 1000°C but partially plastic at 1600°C. The significantly lower coke strength at 1600°C could help explain the smaller coke lump size found near the tuyere level in quenched blast furnaces.